Diabetes in pregnancy: a practical guide for midwives. (2nd July 2019) - Surendran, Aarthi; Dixon, Danielle; Whyte, Martin
Abstract : Diabetes is a growing concern. With the rising incidence of obesity in the younger people, the incidence of diabetes has also increased. This has resulted in more women of childbearing age attending antenatal clinic with a diagnosis of either pre-existing or gestational diabetes. Management of these women is vital to avoid complications in both the mother and the child during pregnancy and childbirth. This article aims to provide a concise guide to the management of diabetes in pregnancy for midwives, who are often the first point of contact for these women.